2020
DOI: 10.3390/molecules25214986
|View full text |Cite
|
Sign up to set email alerts
|

New Lead Discovery of Herbicide Safener for Metolachlor Based on a Scaffold-Hopping Strategy

Abstract: The use of herbicide safeners can significantly alleviate herbicide injury to protect crop plants and expand the application scope of the existing herbicides in the field. Sanshools, which are well known as spices, are N-alkyl substituted compounds extracted from the Zanthoxylum species and have several essential physiological and pharmacological functions. Sanshools display excellent safener activity for the herbicide metolachlor in rice seedlings. However, the high cost of sanshools extraction and difficulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…As of now, various natural products can be used as safeners. Jablonkai noted the relevance of a secondary plant metabolite, cyclic hydroxamic acids with a 1,4-benzoxazin-3-one skeleton, found in cereals such as wheat, maize, and rye, for the catalytic effect of non-enzymatic hydrolysis of 2-chloro-triazine herbicides such as atrazine and simazine to generate non-phytotoxic 2-hydroxy derivatives. , Deng noted that N -alkyl-substituted compounds are obtained from Zanthoxylum species and possess some important physiological and pharmacological functions . Abscisic acid (ABA), as a natural product, is an important phytohormone that participates in many aspects of plant growth and development .…”
Section: Introductionmentioning
confidence: 99%
“…As of now, various natural products can be used as safeners. Jablonkai noted the relevance of a secondary plant metabolite, cyclic hydroxamic acids with a 1,4-benzoxazin-3-one skeleton, found in cereals such as wheat, maize, and rye, for the catalytic effect of non-enzymatic hydrolysis of 2-chloro-triazine herbicides such as atrazine and simazine to generate non-phytotoxic 2-hydroxy derivatives. , Deng noted that N -alkyl-substituted compounds are obtained from Zanthoxylum species and possess some important physiological and pharmacological functions . Abscisic acid (ABA), as a natural product, is an important phytohormone that participates in many aspects of plant growth and development .…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant enzyme activity (e.g., SOD, CAT, and POD) of rice seedlings can be better improved by them compared with metolachlor treatment. 93 Hu et al showed that pretreatment caused an increase in malondialdehyde (MDA) content as well as SOD, CAT, and POD activity in rice seedlings. The combined application of Fen could reverse the MDA accumulation caused by Pre.…”
Section: ■ Other Mechanismsmentioning
confidence: 99%
“…Furthermore, N -alkyl amide derivatives (compound 5 : CH 3 (CH 2 ) 5 CONHCH 2 CH­(CH 3 ) 2 ; and compound 6 : CH 3 (CH 2 ) 5 CONHCH 2 C­(CH 2 )­CH 3 ) were potential safeners for s-metolachlor, which had excellent crop safener activities. The antioxidant enzyme activity (e.g., SOD, CAT, and POD) of rice seedlings can be better improved by them compared with metolachlor treatment . Hu et al showed that pretreatment caused an increase in malondialdehyde (MDA) content as well as SOD, CAT, and POD activity in rice seedlings.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Active substructure splicing, intermediate derivatization methods (IDMs), scaffold hopping, natural product structure optimization, etc. have become the core technologies for finding candidate herbicide safeners. …”
Section: Design Of Novel Herbicide Safeners In Recent Yearsmentioning
confidence: 99%
“…Amide Herbicide Safeners. The chain-shortening method was used by Deng et al 61 The unsaturated long alkyl carbon chains were replaced by saturated and unsaturated alkyl carbon chains of 1−6 carbon atoms, and the structure of sanshools was simplified (Scheme 13). Notably, N-alkyl amide derivatives were synthesized from amines and saturated and unsaturated fatty acids through acylation and condensation via scaffold hopping.…”
Section: ■ Introductionmentioning
confidence: 99%